THE IMPACT OF FESTIVALS AND TRADITIONAL EVENTS ON TOURISM IN THE FERGANA VALLEY - Mamatazizov Faryozbek Pakhlavon o'g'li (Journals Park Publishing, 2025)
The Fergana Valley is considered one of the most fertile, ancient regions of Uzbekistan. Throughout this region, a unique cultural wealth and values are formed, architectural monuments, beautiful natural landscapes, handicrafts and many national traditions are concentrated. At the same time, the annual festival and traditional events in the Fergana Valley serve as one of the important factors in bringing the tourism potential of the area to a high level. These types of activities, on the one hand, contribute to the development of tourism in the country, if it positively affects the cultural and economic well-being of the local population, bringing life to life.
Keywords: Fergana Valley, Tourism, festival, traditional events, cultural heritage, local events, crafts, tourist potential, festival Tourism, Regional Development.